Probiotic evaluation studies and elemental composition of iron-fortified sweet corn milk-based probiotic yogurt - Princy, Geetha (Indian Journal of Dairy Science, 2024)
The market potential of total dairy-based fermented products was estimated to be around Rs.393,050.26 in 2022. Yoghurt is one of the important fermented milk products with numerous nutrition and health benefits but has low iron content. To further improve the nutritional value sweet corn milk was incorporated at 30% along with cow milk and ferrous lactate for the development of iron-fortified probiotic sweet corn blend milk yoghurt. The premix was fermented with 2% probiotic cultures: Streptococcus thermophilus MTCC 1938 and Lactobacillus acidophilus MTCC 447 at 42oC for 4h. It was stored for 16 days under refrigerated conditions. Food grade ferrous lactate hydrate salt was used at different concentrations like 10mg and 20 mg per 100 ml of premix were used for fortification. It proved the addition of ferrous lactate had not affected yogurt characteristics. The elemental composition analysis was done using an X-ray fluorescence spectrophotometer. 20 mg ferrous lactate fortified probiotic sweet corn blend milk yogurt remained acceptable even at 16 days of storage. This iron-fortified probiotic yoghurt serves as a potential fermented milk product for commercial use.